Projected longevities of cardiac implantable defibrillators: a retrospective analysis over the period 2007–17 and the impact of technological factors in determining longevity. Issue 1 (13th August 2019) - Paton, Maria F; Landolina, Maurizio; Billuart, Jean-Renaud; Field, Duncan; Sibley, Jonathan; Witte, Klaus
Abstract: Aims: Implanters of cardiac implantable electronic devices cannot easily choose devices by longevity as usually current models only have projected longevity data since those with known performance are obsolete. This study examines how projected device longevities are derived, the influencing factors, and their roles in guiding model choice. Methods and results: Ninety-eight implantable cardioverter-defibrillator (ICD) and cardiac resynchronization therapy-defibrillator (CRT-D) models released in Europe in 2007–17 were analysed for reported battery capacities, projected longevities for standardized settings stipulated by the French Haute Autorité de Santé (HAS) and manufacturer-chosen settings. Battery capacities and HAS projected longevities increased during the study period. Based on current drain estimation, therapy functions consumed only a small portion (2–7%) of the battery energy for single- and dual-chamber ICDs, but up to 50% (from biventricular pacing) for CRT-Ds. Large differences exist between manufacturers and models both in terms of battery capacity and energy consumption. Conclusion: Battery capacity is not the sole driver of longevity for electronic implantable cardiac devices and, particularly for ICDs, the core function consume a large part of the battery energy even in the absence of therapy. Providing standardized current drain consumption in addition to battery capacity may provide more meaningful longevity information among implantable electronic cardiac devices.